Virtual Worlds: A New Environment for Constructionist Learning - Savage, Timothy; Girvan, Carina (My University, 2019)
Virtual worlds have the potential to provide a new environment in which to engage learners in constructionist activities. However, they were not designed for education and have features and affordances which are not found in traditional constructionist environments. These may limit the pedagogy in action and/or provide new opportunities with which to transform constructionist pedagogy in practice, but to date there has been no research on these issues. To address this, we explore constructionism in action in the virtual world Second Life. This is the first study to examine the theoretical alignment of pedagogy and technology in practice. An exploratory case study of a purpose-built constructionist learning experience was conducted. The experience was designed based on the theoretical alignment of pedagogy and technology and implemented with 24 postgraduate students over four weeks. Open non-directive interviews, chat logs, constructed artefacts, learners’ written reflections and observations were collected and analyzed using the constant comparative approach. The findings provide insights into how learners engage in meaningful artefact construction, highlight the role of avatars and draw attention to the importance of the designed space. New opportunities for distributed constructionism are identified. We conclude that virtual worlds are effective environments for constructionist learning.
PUBLISHED
Keywords: Constructionism; Virtual worlds; Pedagogy; Constructionist theory; Avatars; Learning; Turtle; Scratch; 3D; Information technology in education; Virtual Worlds